2008
DOI: 10.1523/jneurosci.2869-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Human Temporoparietal Junction and MT/V5+ to the Timing of Interception Revealed by Transcranial Magnetic Stimulation

Abstract: To intercept a fast target at destination, hand movements must be centrally triggered ahead of target arrival to compensate for neuromechanical delays. The role of visual-motion cortical areas is unclear. They likely feed downstream parietofrontal networks with signals reflecting target motion, but do they also contribute internal timing signals to trigger the motor response? We disrupted the activity of human temporoparietal junction (TPJ) and middle temporal area (hMT/V5ϩ) by means of transcranial magnetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 75 publications
7
80
3
Order By: Relevance
“…This time shift indicates an influence of the orientation relative to visual gravity on response timing that could be attributed to the anticipation of the effects of visual gravity on self-motion along the vertical, but not the horizontal orientation. Finally, precision in TTP estimates was higher during vertical fall than when traveling at constant speed along the vertical orientation, consistent 1 3 network of areas including the posterior-insula and the temporo-parietal junction (Indovina et al 2013, Maffei et al 2010Miller et al 2008;Bosco et al 2008).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This time shift indicates an influence of the orientation relative to visual gravity on response timing that could be attributed to the anticipation of the effects of visual gravity on self-motion along the vertical, but not the horizontal orientation. Finally, precision in TTP estimates was higher during vertical fall than when traveling at constant speed along the vertical orientation, consistent 1 3 network of areas including the posterior-insula and the temporo-parietal junction (Indovina et al 2013, Maffei et al 2010Miller et al 2008;Bosco et al 2008).…”
Section: Introductionsupporting
confidence: 57%
“…On the other hand, studies on interception of moving objects and on estimates of time intervals showed that a priori knowledge about gravitational acceleration, combined with realistic cues about the orientation and size of the visual scene, can influence response timing (Moscatelli and Lacquaniti 2011;Zago et al 2009;Miller et al 2008;Bosco et al 2008;Senot et al 2005;McIntyre et al 2001). This a priori knowledge is thought to be stored in a visual-vestibular Abstract By simulating self-motion on a virtual rollercoaster, we investigated whether acceleration cued by the optic flow affected the estimate of time-to-passage (TTP) to a target.…”
Section: Introductionmentioning
confidence: 99%
“…One can hypothesize, therefore, that the difference in corticospinal excitability between the conditions may be due to the two conditions involving the dorsal and ventral streams and that the former allows a more controlled buildup of responserelated activation. Bosco et al (2008) have recently presented evidence that the dorsal stream provides internal timing signals used for interceptions and its disruption by means of TMS over MT/V5 ϩ can be detrimental to performance in this type of task. Merchant and colleagues (2004a,b) also found evidence that area 7a of monkeys, located in the inferior parietal lobule in the dorsal visual stream, can provide timing signals to trigger interceptions.…”
Section: Discussionmentioning
confidence: 99%
“…body schema (Blanke et al, 2005;Grossman, et al, 2005), gravity (Bosco, Carrozzo, & Lacquaniti, 2008), and beliefs (Young, Camprodon, Hauser, Pascual-Leone, & Saxe, 2010)]. Although this predictive function could be an instance of a general Bayesian inference mechanism (Friston, 2010;Friston, Kilner, & Harrison, 2006), the pSTS appears to be distinctively able to construct predictions based on information from several different categories.…”
Section: U N D E R S T a N D I N G C O M M U N I C A T I V E A C T Imentioning
confidence: 99%
“…Functionally, we assessed the effects of rTMS during a visual tracking task that used exactly the same timeseries of stimuli shown during the communication task, but with no communicative requirements. Anatomically, we contrasted the effects of stimulating the right pSTS with those evoked by stimulating a contiguous homotopic region involved in integrating position information when viewing moving objects [left MT+, (Bosco, et al, 2008;Maus, Ward, Nijhawan, & Whitney, 2012)], a function required for processing the stimuli used during the communication and the visual tracking tasks.…”
Section: U N D E R S T a N D I N G C O M M U N I C A T I V E A C T Imentioning
confidence: 99%